Cordial Labeling for Swastik Graph - Jagruti C. Kanani (International Journal of Mathematics And its Applications, 2017)
I studied a new graph which is called swastik graph. I proved that the swastik graph is cordial. I have investigated some swastik graph related families of connected cordial graphs. I proved that path union of swastik graph, cycle of swastik graph and star of swastik graph are cordial.